Penerapan E-Learning Â¬Platform Google Classroom Untuk Menjawab Tantangan Revolusi Industri 4.0 - Yolandari, Andhita; Fithri Meuthia, Reno; Fontanella, Amy (Akuntansi dan Manajemen, 2020)
This research is motivated by a change in the learning system as a result of the 4.0 industrial revolution. This research uses the theory of Technology Acceleration Model (TAM) developed by Fred. D. Davis in 1986. The purpose of this study was to investigate the application of the Google classroom e-learning platform to answer the challenges of the Industrial Revolution 4.0. in Accounting Department in the Polytechnic of Padang. Data gethered using a questionnaire. The population of the study were active students in the Accounting Department of the State Polytechnic of Padang in the 2018/2019 school year with cluster sampling and 241 respondents. The results of this study indicate that perceived usefulness has a positive and significant effect on student interest in using google classroom, and perceived ease of use has a positive and significant effect on student interest in using google classroom. Based on the results of this study indicate several things that must be considered by the Accounting Department of the Padang State Polytechnic before applying the use of technology.